(untitled) (Research, Society and Development, 2021)
Leprosy is a chronic infectious disease. Its cause is Mycobacterium leprae, a frankly gram-positive and resistant acid-alcoholic bacterium that can infect peripheral nerves. This study aimed to describe the epidemiological aspects of leprosy in the city of Caxias-MA. This is a documentary, descriptive, retrospective and quantitative study, carried out from 2013 to 2017, using data from the Ministry of Health’s Notifiable Diseases Information System (SINAN). This study evaluated 349 cases of leprosy in the period from 2013 to 2017 in the municipality of Caxias in the state of Maranhão. The highest coefficients were recorded in 2013 (6.15 / 10000) and 2015 (5.03 / 10000). Regarding the profile of the identified patients, there was a male prevalence with 191 (54.7%) of the cases, in that there was a predominance of the age group from 50 to 59 years (18.6%), the evaluation of the operational classification shows that the multibacillary form was the most frequent (74.5%); as to the percentage of skin lesions due to leprosy, the highest rate is two to five injuries with 151 (43.3%) of the cases, and with regard to the therapeutic scheme, 260 (74.5%) received multibacillary multidrug treatment (PTQ / MB) of 12 doses. Leprosy is still considered a neglected disease, although there are public policies aimed at eradicating it, we are still on a long and slow path to eliminate the disease. However, many screening actions and activities are intensifying for the early diagnosis and treatment of leprosy in order to reduce the high rates of multibacillary cases.